TEACHERS’ ABILITY IN WRITING SCIENTIFIC ARTICLE - Nur Aisyah Zulkifli (Kutubkhanah, 2017)
Based on the regulation of The Minister of State for Administrative inveiglement Number 16 Year 2009 regarding Position of Teacher Functional score and credit figures, teachers are required to conduct professional development sustainable by writing scientific article published in scientific journals. UIN SUSKA through Suara Guru Journal helps teachers in their publications. In fact, there were still found teachers who negligent in writing article. Therefore, writer consider very important to examine in depth and explain the extent to which the teacher's ability to write articles and to describe whether the teachers works could be published in “Suara Guru’ Journal of UIN Suska Riau. To answer the question, researcher would like to conduct the field rsearch in qualitative study